Analysis and Design of OSH System of PT ASI Welding Department During the Pandemic - Maharani Pradeshi Duarsa, Putu Utari; Sukapto, Paulus (Jurnal Improsci, 2024)
PT Adyawinsa Stamping Industries (ASI) is one of the automotive industry companies operating during the COVID-19 pandemic. As a result, there are government policies that companies need to follow to continue operating safely. Policies related to COVID-19 need to be implemented in conjunction with the company's Occupational Safety and Health (K3). Based on interviews conducted with company representatives, an evaluation is required in order to find out the implementation of policies related to COVID-19 in line with K3 in the Welding Department. Initial observations are carried out to determine the actual conditions and identify operational activities. K3 evaluation is carried out by applying the Failure Mode and Effect Analysis (FMEA) method to determine the potential hazards. The results of the FMEA evaluation provide a series of hazard priorities and potential dangers that guide the design of improvement proposals. The proposal's design was implemented using the Participatory Ergonomics (PE) method involving several stakeholders. The improvement proposal is the result of identifying the needs of the Welding Department workers based on discussions conducted through the PE method. The discussion resulted in a proposed design in the form of reviewing and controlling SOPs and conditions in the field, implementing periodic safety training, and installing instruments to remind workers of K3 in operational activities. The instruments designed in the study are several infographic materials regarding implementing K3 and COVID-19 prevention in the workplace.